Bentuk Pertunjukan Barong Singo Kubro di Desa Balongrejo, Kecamatan Banjarejo, Kabupaten Blora - Widya Ayu Angelica; R. Indriyanto (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The art of barongan is a form of art found in Blora Regency, Central Java. One of the barongan groups that still exists today is the Barong Singo Kubro. It is a form of traditional performing art that has developed in Balongrejo Village, Banjarejo District, Blora Regency. The performance has an initial pattern, a core pattern, and a final pattern, and it contains elements of performance such as themes, characters, movements, costumes, make-up, stage arrangement, and props. This research aims to describe the form of the performance. The approach used is descriptive qualitative with techniques of observation, interviews, and documentation. The results of the study indicate that the performance is arranged in a colossal manner, consisting of an opening barong, small bujangganong, large bujangganong, kerah barongan, jaranan, dadak merak, extreme attractions, and a closing barongan.